Review of Orbiniidae (Annelida, Sedentaria) from Australia - Zhadan, Anna (Zootaxa, 2020)
The present study is a review of all known Australian and New Zealand orbiniid species with their redescription based mainly on the collection of the Australian Museum (Sydney). A total of 28 species were examined: seven species of Scoloplos, three species of Leitoscoloplos, five species of Leodamas, three species of Naineris, two species of Orbinia, three species of Phylo, one species of Proscoloplos, and four species of Protoariciella. Leodamas australiensis (Hartmann-Schröder, 1979) is the new combination. Illustrated descriptions and an identification key for Australian and New Zealand orbiniids are provided.